Literacies in language education : a guide for teachers and teacher educators - Paesani, Kate; Menke, Mandy R. (Georgetown University Press, 2023)
"Some pedagogists have struggled with what they see as a lack of literacy among learners immersed in the communicative approach to learning and how to bridge this gap as learners reach the upper levels. Literacies in Language Education introduces and provides practical guidance on how to teach world languages using a multiliteracies approach, which focuses on critical engagement with texts and intercultural development to further language learning. Melding the sometimes conflicting interests in language depts of literature and linguistics, the authors embrace an expanded understanding of literacies to capture the dynamism of language and its contexts of use; the importance of preparing students to interact with the range of text types they will encounter in their academic, workplace, and personal lives; and the multicultural and multilingual landscape of secondary and postsecondary language classrooms. The book provides clear and practical guidance about what the approach is, its benefits, and how to create curricula for it; how to use the approach in teaching; and how to train teachers to use the approach--each a key access point to pedagogical change. This book provides teachers and program admins immediate steps to take toward designing and implementing this approach in their classes and curricula. The authors are well-known in this area for their teacher training at CARLA, a well-respected center at the U of MN. CARLA hosts multiple workshops on the topic annually and is invited to do so around the country; they will adopt this book in those workshops."--